Modern contraceptive use among women in Uganda: An analysis of trend and patterns (1995-2011) - Andi, Jimmy Ronald; Wamala, Robert; Ocaya, Bruno; Kabagenyi, Allen (African population studies, 2014)
There is an extensive body of literature concerning modern contraceptive use among women in Uganda. A questionable aspect however is whether the impact of factors associated with modern contraceptive use has remained the same in the recent past. Demographic Health Survey (DHS) data of women in the period 1995-2011 was adopted to establish an understanding of this issue. The focus in the investigations was none pregnant sexually active women. Variations in patterns of modern contraceptive use were assessed by socio-economic and demographic characteristics of women using a logistic regression based on a complex survey design. In the results, an upward trend in modern contraceptive use - from 11.6% in 1995 to 32.1% in 2011 - shows that progress has been made in this regard. Increased odds of modern contraceptive use across the study period were noted among women with primary and post-primary education, those in urban areas, women in the higher wealth quartiles and those with a higher number of surviving children (p < 0.01). Further, reduced odds of modern contraceptive use across the study period were noted among married women and those in cohabiting relationships (p < 0.05). The study however demonstrates variations in the impact of these factors across the study period. All the same, efforts towards enhancing modern contraceptive use in the near future should focus on enhancing: (i) literacy levels of woman particularly, (ii) access to and affordability of the services, and (iii) awareness campaigns on family planning use targeting both men and women.
Keywords: Family planning utilization; Modern contraceptive use; Uganda